2018
DOI: 10.1111/joic.12538
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the impact of successful chronic total occlusion percutaneous coronary intervention on left ventricular systolic function and reverse remodeling

Abstract: Successful CTO PCI is associated with a statistically significant improvement in LV ejection fraction and decrease in LV end-systolic volume, that may reflect a beneficial effect of CTO recanalization on LV remodeling. The clinical implications of these findings warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 48 publications
2
30
0
1
Order By: Relevance
“…Several observational studies 26–31 and two RCTs 32,33 have reported that successful CTO PCI is associated with improvement in the quality of life, reduced need for CABG, improved left ventricular (LV) function, and LV reverse remodeling compared with failed revascularization. The retrograde approach is currently an essential tool for achieving high success rates, especially in complex lesions where the antegrade approach is not technically feasible or fails 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies 26–31 and two RCTs 32,33 have reported that successful CTO PCI is associated with improvement in the quality of life, reduced need for CABG, improved left ventricular (LV) function, and LV reverse remodeling compared with failed revascularization. The retrograde approach is currently an essential tool for achieving high success rates, especially in complex lesions where the antegrade approach is not technically feasible or fails 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Michael Megaly et al and showed a statistically signi cant increase in LVEF (3.8%, 95% CI 3.0-4.7, P < 0.0001) as compared with baseline [13] . Additionally, in our study, lower LVEF (LVEF 0.5) and LM disease predicted a worse probability for cardiac death.…”
Section: Discussionmentioning
confidence: 91%
“…22 A recent meta-analysis of 34 studies with a total of 2,804 patients, by Megaly et al, showed that successful revascularization of a CTO is associated with a significant increase in LVEF, especially in those with lower baseline values. 24…”
Section: Ventricular Function In Percutaneous Coronary Intervention Omentioning
confidence: 99%
“…Finally, of the most frequent extra-cardiac periprocedural complications, those related to vascular access are notable. In recent years, attention has been paid to the type of access,with the aim of minimizing the use of femoral access and of large introducer sheaths (8 Fr) 24.…”
mentioning
confidence: 99%